Determinação de minerais por diferentes métodos analíticos em leite de cabras sem raça definida (srd) criadas na região do cariri paraibano, Brasil - Carvalho, Caroline Uchôa Souza (2016)
The goat milk is a food matrix of high nutritional value, low allergenic power when compared to cow's milk and is more digestible and easily accessible. Currently, the goat has been growing, especially in semi-arid regions where these animals adapt to the climatic conditions. The cariri region of Paraíba is a semi-arid climate of the region where the creation model is extensive, with small herds and smallholdings, often being the main source of household income. In this region, the herds are predominantly animals mongrel and/or crossbred animals, the composition of minerals is still poorly understood. This study aimed to compare the different methodologies used in the determination of minerals in undefined breed goats (SRD) resulting from crossing with purebred animals reared in the semi-arid northeast of Brazil. The milks were collected from SRD goats resulting from the crossing of the purest lineage breeds, quote: Saanen, Toggenburg and Parda + Toggenburg belonging to three producers in a dairy cooperative in the town of Monteiro/PB. For comparison, milk samples were subjected to the determination of calcium, iron, phosphorus and sodium by traditional techniques (titration and spectrophotometric methods) and more advanced techniques (ICP-OES and EDX-RF). We observed the influence of the dominant phenotype to undefined breed goats in the concentration of most minerals analyzed, especially when using ICP-OES technique. Difference between methods used for most mineral studied in each type of milk, whose detected values were higher when used traditional techniques, except for the sodium. Furthermore, the RF-EDX technique may be singled out as an analytical alternative to obtain quantitative data for iron and phosphorus in goat milk. Although they were used conventional methods for the quantification of mineral elements such as titration and spectrophotometric, the values found for minerals were similar to those reported by research using instrumental methods and, therefore, greater sensitivity and accuracy. This data shows the possibility of using simpler methods, as an alternative to detect these minerals, especially in the absence of the availability of more sophisticated equipment and not always as accessible in food quality control laboratories.